Fraud Heptagon Dan Religiusitas Terhadap Kecurangan Organisasi - Serly, Serly; Viviany, Viviany (Universitas Gorontalo, 2025)
This study aims to analyze corporate fraud by integrating the fraud heptagon model with the dimension of religiosity. The data used in this research are derived from the annual reports of companies listed on the Indonesia Stock Exchange for the 2018–2022 period. The study employs the fraud heptagon model, which considers nine key factors of fraud: incentives, pressure, opportunity, attitude, justification, capability, arrogance, ignorance, greed, and religious values in curbing unethical behavior and fraud. The findings indicate that management incentives have a significant influence on corporate fraud, while financial pressure exhibits a negative relationship with fraud. However, factors such as religiosity were found to have no significant impact in the examined context. This article aims to provide meaningful contributions to the understanding and mitigation of fraud.